Extensive Dissection at No. 12 Station During D2 Lymphadenectomy Improves Survival for Advanced Lower-Third Gastric Cancer: A Retrospective Study From a Single Center in Southern China - Dai, Weigang; Zhai, Er-Tao; Chen, Jianhui; Chen, Zhihui; Zhao, Risheng; Chen, Chuangqi; Yuan, Yujie; Wu, Hui; Cai, Shirong; He, Yulong (Frontiers in Oncology, 2022)
Background: D2 lymphadenectomy including No. 12a dissection has been accepted as standard surgical management of advanced lower-third gastric cancer (GC). The necessity of extensive No. 12 nodes (No. 12a, 12b and 12p) dissection remains controversial. This study aims to explore its impact on long-term survival for resectable GC. Methods: From 2009 to 2016, 353 advanced lower third GC patients undergoing at least D2 lymphadenectomy during a radical surgery were included, with 179 patients receiving No. 12a, 12b and 12p dissection as study group. 174 patients with No. 12a dissection were employed as control group. Surgical and long-term outcomes including 90-day complications incidence, therapeutic value index (TVI), 3-year progression-free survival (PFS), and 5-year overall survival (OS) were compared between both groups. Results: No. 12 lymph node metastasis was observed in 20 (5.7%) patients, with 10 cases in each group (5.6% vs. 5.7%, P=0.948). The metastatic rates at No. 12a, 12b and 12p were 5.7%, 2.2% and 1.7%, respectively. The incidence of 90-day complications was identical between both groups. Extensive No. 12 dissection was associated with increased TVI at No. 12 station (3.9 vs. 0.6), prolonged 3-year PFS rate (67.0% vs. 55.9%, P=0.045) and 5-year OS rate (66.2% vs. 54.0%, P=0.027). The further cox-regression analysis showed that the 12abp dissection was an independent prognostic factor of improved survival (P=0.026). Conclusion: Adding No. 12b and 12p lymph nodes to D2 lymphadenectomy might be effective in surgical treatment of advanced lower third GC and improve oncological outcomes compared with No. 12a-based D2 lymphadenectomy.